2014
DOI: 10.1155/2014/540276
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosive Properties of Poly(o‐phenylenediamine)/ZnO Nanocomposites Coated Stainless Steel

Abstract: Poly(o-phenylenediamine) and poly(o-phenylenediamine)/ZnO (PoPd/ZnO) nanocomposites coating were prepared on type-304 austenitic stainless steel (SS) using H2SO4acid as electrolyte by potentiostatic methods. Fourier transforms infrared spectroscopy and scanning electron microscopy techniques were used to characterize the composition and structure of PoPd/ZnO nanocomposites. The corrosion protection of polymer coatings ability was studied byEocp-time measurement, anodic and cathodic potentiodynamic polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The decrease in the corrosion current indicates that PZWC and PWC coatings can rely on the reversible redox properties of the polymer materials [32]. In the presence of ZnO nanocomposites, he corrosion resistance of the coating will also increase [33,34] anodic reaction by acting as a barrier layer between electrode surface and corrosive environment [24,35]. The protection efficiency (PE%) of coatings was also calculated by the following equation [36]:…”
Section: Corrosion Protection Evaluation Of Poly(o-phenylenediamine)-mentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the corrosion current indicates that PZWC and PWC coatings can rely on the reversible redox properties of the polymer materials [32]. In the presence of ZnO nanocomposites, he corrosion resistance of the coating will also increase [33,34] anodic reaction by acting as a barrier layer between electrode surface and corrosive environment [24,35]. The protection efficiency (PE%) of coatings was also calculated by the following equation [36]:…”
Section: Corrosion Protection Evaluation Of Poly(o-phenylenediamine)-mentioning
confidence: 99%
“…To the best of our knowledge, few literature on the coating of PoPD-ZnO nanocomposites has been published as corrosion protection for carbon steel in chloride media [24]. In this paper, we used carbon steel as the substrate, and prepare nanocomposite coatings composed of PoPD and PoPD-ZnO by chemical oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymer/ZnO nanocomposites coating were prepared on type-304 austenitic stainless steel (SS) using H 2 SO 4 acid as electrolyte by potentiostatic methods. It was found that ZnO nanoparticles improve the barrier and electrochemical anticorrosive properties of polymer [81]. Electrically conducting polypyrrole (PPy)-iron group (Ni, Co, Fe and their alloys) composite films have been electrodeposited at cathodic process to give ''tailored'' soft and hard magnetism.…”
Section: Polymeric Matrix Nanocomposites Pncsmentioning
confidence: 99%
“…This is due to the presence of the poly(aniline-co-o-toluidine) in the coating system that accepts electrons from the metal and gives them to oxygen. This reaction assists the formation of a passive oxide layer at the polymer/metal interface, which lowers the corrosion rate and shifts the E corr to noble potential [33,34]. However, the corrosion resistance of specimen OPF4 was found to degrade severely in 3.5 wt.% NaCl solution (Table 2).…”
Section: Tafel Plotsmentioning
confidence: 99%
“…In the field of corrosion also, various works have been carried out to design PANI/inorganic filler composite coatings with good anti corrosive properties [18][19][20][21][22][23]. Among these inorganic fillers, flyash is an excellent reinforcing material for polymeric materials.…”
Section: Introductionmentioning
confidence: 99%